Pengaruh Jurnal Membaca Digital terhadap Kemampuan Literasi Siswa Kelas V Sekolah Dasar - Jefri Nur Fahmi; Siti Rochmiyati (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The development of society 5.0 requires good literacy skills. Good literacy skills are useful for making choices and filtering the quick advancement of data innovation that is at present happening. The proficiency abilities of primary school understudies in light of the PISA study are still generally low. There is a need for teacher innovation to improve students' literacy skills, especially in elementary school. One of the innovations carried out is using a digital reading journal. The point of this research is to decide the impact of utilizing digital reading diaries on the proficiency abilities of 5th grade primary school student. This exploration utilizes a trial plan pretest-posttest design. The subjects of this researchs were 20 students at SD Negeri Kalisari, Temon, Kulon Progo, 20 students as the control class and 20 students in class V at SD Negeri Janten, 20 students as the experimental class. Research data was collected using a multiple choices test instrument which had been tested for validity and reliability using formula pearson correlation formula via the spss 25 application. The collected data was tested for normality and homogeneity as a prerequisite for hypothesis testing. The data in this study were analyzed using the t-test via the spss 25 application. From the results of the t-test, values ​​were obtained sig 2-tailed of 0.002 can be interpreted as a difference in the literacy abilities of experimental class students and control class students. From the results of the t-test, the calculated t value was 3.256. Based on these results, the calculated t value > t table for db 38. The t table value is 2.059 for 5%alpha values and 2.796 for 1% alpha value. Based on these results, it can be concluded that the use of digital reading journals has a very significant impact on the literacy skills of class V students at SD Negeri Janten.